The effect of environmental performance, firm size, and profi tability on environmental disclosure - Jane Adriana; Nurul Hasanah Uswati Dewi (Universitas Hayam Wuruk Perbanas, 2018)
These studies aims to examine and analyze the effect of environmental performance, fi rm size, and profi tability on environmental disclosure in mining companies, participating in PROPER Program and are listed on the Indonesia Stock Exchange (IDX) period 2012-2015. This study is an explanatory study using quantitative approach. The sample consists of 52 respondents from 13 companies x 4 (period 2012-2015). There were 4 outlier data obtained, therefore the final sample used is 48 selected using a purposive sampling technique. The data were analyzed using a classical assumption test and multiple linear regression analysis. The results show that environmental performance and fi rm size have positive effect on environmental disclosure, while profi tability has no effect on environmental disclosure. This study has limitations on the number of samples, because there are still many companies that have not participated in the PROPER program. It can be implied that this study illustrates that the companies to be more concerned about the environment. Therefore, it is recommended that further research use more research samples.